Inviting Newton to Visit the Delivery Room the Role of Gravity During Childbirth - Stark M; Mynbaev O; Malvasi A; Tinelli A (Dove Medical Press, 2023)
Michael Stark,1 Ospan Mynbaev,1 Antonio Malvasi,1,2 Andrea Tinelli1,3 1The New European Surgical Academy, Berlin, Germany; 2Department of Obstetrics and Gynecology, Santa Maria Hospital G.V.M. Care & Research, Bari, Italy; 3Department of Obstetrics and Gynecology and CERICSAL (CEntro di RIcerca Clinico SALentino), Veris delli Ponti Hospital, Scorrano, Lecce, ItalyCorrespondence: Michael Stark, Email mstark@nesacademy.orgAbstract: Throughout history, the upright position was the norm for most deliveries. However, due to cultural reasons, this practice was changed in the 17th century, and since then, the majority of deliveries have been conducted with the parturient lying on her back. The aim of this review article is to challenge the nowadays recumbent birth position and to emphasize the added value of gravity to the childbirth. Physiologically there is a strong argument for delivering in an upright position due to the significant role of gravity. The baby’s presenting part does not move back between contractions as happens in today’s recumbent position when due to the anatomy of the pelvis, the presenting part moves uphill. In this position, the second stage is shorter, and the signal for active pushing occurs spontaneously. It is recommended that any parturient should be informed about the risks and benefits of each birthing option to decide the birthing position that suits her.Keywords: labor position, birth, upright birth, delivery